Patients’ and Parents’ Perceptions of Appearance in Scoliosis Treated with a Brace: A Cross-Sectional Analysis - Misterska, Ewa (Springer US, 2013)
The perspective of trunk deformity is a matter of special concern for adolescent idiopathic scoliosis (AIS) patients. No research group has ever reported interviewing patients and their parents regarding differences in perception of body appearance in the course of Cheneau brace treatment. We aimed to investigate the level of agreement in the field of concerns and perceptions of spinal appearance in relation to brace- and scoliosis-related data between parents and female patients with AIS, treated with a Cheneau brace, by means of the Spinal Appearance Questionnaire-pl (SAQ-pl). In this cross-sectional study forty-one pairs of parents and female patients with AIS were asked to separately complete the Polish versions of the Spinal Appearance Questionnaire-pl patient form (SAQ-pl patient form) and the SAQ-pl parent form. Age of patients was 13.60 years SD 1.60 (range 10–17). Patients scored 2.70 (SD 0.60) and parents scored 2.70 SD 0.60 in the total score of the SAQ-pl. The study groups do not differ significantly in regards to the SAQ-pl results. The percentage of consistent answers on SAQ-pl items ranges from 34.10 % (item 20) to 78 % (item 8). Height, age and brace-wearing time per day, were significantly related to the differences in the patient-parent General perception of body shape (r(s) = −0.51, r(s) = −0.34, r(s) = 0.36, respectively). Parents and female patients with AIS have similar concerns and perceptions of spinal appearance. The discrepancies in General perception of spinal appearance between parents and AIS females decrease with age of patient. Parental emotional support may contribute to minimizing the risk factors of psychological impairment, especially in late adolescents with AIS.